PENGARUH SELF-DISCLOSURE DI SOCIAL MEDIA TERHADAP PENGAMBILAN KEPUTUSAN DALAM MENTAL HEALTH PADA GENERASI Z - Sriyono, Sriyono; Ameliya, Dinda Nur; Chariri, Muchammad Iqbal (Ensiklopedia of Journal, 2024)
This research aims to determine the influence of self-disclosure on social media on generation Z's mental health decision making. Self-disclosure is consciously disclosing information about oneself that was previously unknown to others. In this research, the literature review method was used. The focus of this research is on self-disclosure in mental health in Gen Z so that individuals are free to express their feelings or emotions. The results obtained from this research are that openness to other people makes you feel calm because there is a sense of comfort and trust in other people.Keyword: Generationi Z; Self-Disclosure; Mental Healt; Decision Making